2020
DOI: 10.1186/s12885-020-07571-0
|View full text |Cite
|
Sign up to set email alerts
|

Targeted nanopore sequencing for the identification of ABCB1 promoter translocations in cancer

Abstract: Background Resistance to chemotherapy is the most common cause of treatment failure in acute myeloid leukemia (AML) and the drug efflux pump ABCB1 is a critical mediator. Recent studies have identified promoter translocations as common drivers of high ABCB1 expression in recurrent, chemotherapy-treated high-grade serous ovarian cancer (HGSC) and breast cancer. These fusions place ABCB1 under the control of a strong promoter while leaving its open reading frame intact. The mechanisms controlling high ABCB1 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Signal transmission between stromal cells and tumor cells.findings, p-gp was hypothesized to be a drug efflux pump encoded by the ABCB1 gene(73). The experiment conducted by L.V.…”
mentioning
confidence: 99%
“…Signal transmission between stromal cells and tumor cells.findings, p-gp was hypothesized to be a drug efflux pump encoded by the ABCB1 gene(73). The experiment conducted by L.V.…”
mentioning
confidence: 99%
“…Nanopore technology gives a new insight to health and disease, from cancer, immunology, to neuroscience. The representing references are [61][62][63][64][65][66] Detection of microbes…”
Section: Clinical Researchmentioning
confidence: 99%
“…It shows that nanopore sequencing technology has a certain application prospect in the detection of a series of structural variations with good characteristics. Williams et al also demonstrated that targeted nanopore sequencing is an effective way to identify ABCB1 structural variation in THP-1AML cells and HGSCs [63].…”
Section: Structure Variationsmentioning
confidence: 99%
“…In addition, Williams et al. [ 126 ] applied targeted nanopore sequencing and identified ABCB1 structural variants in THP-1 AML cells and high-grade serous ovarian cancer cells. In the context of non-small-cell lung cancer, Sakamoto et al.…”
Section: Applications Of Tgs Technologies In Cancermentioning
confidence: 99%